Chlorination of isothiazolinone biocides: kinetics, reactive species, pathway, and toxicity evolution. (1st September 2022) - Wang, Wen-Long; Nong, Yu-Jia; Yang, Zheng-Wei; Wu, Qian-Yuan; Hübner, Uwe
Highlights: The reactivities of isothiazolinone with HOCl, Cl2 O, and Cl2 were determined Cl2 O dominated the chlorination of isothiazolinone biocides at circumneutral pH Cl2 became the main contributor of biocide oxidation at acidic pH and added Cl − FAC removed the toxicity and parent biocides via preferential oxidation of S-atom Abstract: Due to the Covid-19 pandemic, the worldwide biocides application has been increased, which will eventually result in enhanced residuals in treated wastewater. At the same time, chlorine disinfection of secondary effluents and hospital wastewaters has been intensified. With respect to predicted elevated exposure in wastewater, the chlorination kinetics, transformation pathways and toxicity evolution were investigated in this study for two typical isothiazolinone biocides, methyl-isothiazolinone (MIT) and chloro-methyl-isothiazolinone (CMIT). Second-order rate constants of 0.13 M −1 ·s −1, 1.95 × 10 5 M −1 ·s −1 and 5.14 × 10 5 M −1 ·s −1 were determined for the reaction of MIT with HOCl, Cl2 O and Cl2, respectively, while reactivity of CMIT was around 1-2 orders of magnitude lower. While chlorination of isothiazolinone biocides at pH 7.1 was dominated by Cl2 O-oxidation, acidic pH and elevated Cl − concentration favored free active chlorine (FAC) speciation into Cl2 and increased overall isothiazolinone removal. Regardless of the dominant FAC species, the elimination of MIT and CMIT resulted in an immediate loss of acute toxicity under all experimental conditions, which was attributed to a preferential attack at the S-atom resulting in subsequent formation of sulfoxides and sulfones and eventually an S-elimination. However, chlorination of isothiazolinone biocides in secondary effluent only achieved <10% elimination at typical disinfection chlorine exposure 200 mg·L −1 ·min, but was predicted to be remarkably increased by acidizing solution to pH 5.5. Alternative measures might be needed to minimize the discharge of these toxic chemicals into the aquatic environment. Graphical abstract: Image, graphical abstract